Midterm outcome of mitomycin C augmented trabeculectomy in open angle glaucoma versus angle closure glaucoma - Maheshwari, Devendra (Indian J Ophthalmol, 2019)
PURPOSE: The purpose of this study is to evaluate the efficacy and safety of Trabeculectomy with Mitomycin C in Open angle glaucoma versus Angle closure glaucoma. METHODS: The medical records of patients who underwent Trabeculectomy with Mitomycin C were reviewed and followed for three years, divided into two groups: group 1: Open Angle Glaucoma (n = 41) and group 2: Angle Closure Glaucoma (n = 67). Success criterion was measured as Intraocular Pressure ≤21 mmHg with (qualified) or without (complete) use of Antiglaucoma medications. RESULTS: A total number of 108 eyes of 137 patients were undertaken. Mean preoperative Intraocular pressure in group 1 was 31.4 ± 10.5 mmHg and in group 2 was 33.1 ± 9.4, which reduced to 10.5 ± 3.4, 10.5 ± 2.6, 11.6 ± 3.6, 11.0 ± 2.7, 11.0 ± 2.7 in group 1 and 10.9 ± 2.8, 12.0 ± 3.8, 12.8 ± 4.9, 12.4 ± 3.9, 12.4 ± 3.7 in group 2 with P value = 0.566, 0.032, 0.168, 0.049, 0.049 at three, six months, one, two, three years, respectively, with P < 0.001 at each visit. The number of Antiglaucoma medications was reduced from 0.75 ± 0.89 to 0.43 ± 0.55 at 3 yrs (P = 0.002). At 36 months follow-up, overall, 50.0% and 48.2% of eyes achieved complete and qualified success, respectively. Sub-group analysis showed that the success rate was higher in group 1 (68.3%) compared to group 2 (55.2%). Overall, complications such as hypotony (1.8%), choroidal detachment (2.8%), encapsulated bleb (2.8%), and bleb leakage (1.8%) were encountered. CONCLUSION: Primary Trabeculectomy with Mitomycin C is a safe and effective means of controlling Intraocular Pressure in both groups with good success and low rates of sight-threatening complications.